Teacher enthusiasm as a moderator in the relationship between teacher self-efficacy, teacher competence, and sustainable student learning - Ke, Yang; Razali, Fazilah; Abdul Aziz, Nor Azni (Creative Publishing House, 2024)
Teachers are the most popular source of student learning, and many studies confirm that good teachers lead to students' learning. This research aims to explore the influence of teacher self-efficacy and teacher competence on students' learning. The paper also investigated the moderating role of teacher enthusiasm in the relationship between teacher self-efficacy, teacher competence, and students' learning. Data collected through convenience sampling from 329 respondents were analyzed using the PLS-SEM approach. The results of the study revealed that teacher self-efficacy and students' learning are positively related. The results also provided support for the positive impact of teacher competence on student learning. Finally, the results showed that teacher enthusiasm moderated the effect of teacher self-efficacy and teacher competence on students' learning. Thus, the study suggests that investing in teacher self-efficacy and competence, as well as supporting teacher enthusiasm, can enhance students' learning.